The Relationship between Tax Revenue and Economic Growth in Malaysia - Sharifah Sabrina, Syed Ali; Teh, Siew Wai (2023)
The goal of this study is to examine the relationship between Malaysia economic growth and tax revenue. The data were taken from year 2011 to 2020 from the World Bank and OECD. The data were analyzed using the descriptive analysis, correlation, Variance Inflation Factor (VIF), and Ordinary Least Squares (OLS) research method. The research reveals a high and positive link between OT and GDP and between SCC and GDP, a very strong and positive relationship between PCG and GDP, a very weak and negative relationship between TGS and GDP, and a moderate and negative relationship between TP and GDP. In conclusion, the study on the relationship between tax revenues and economic growth in Malaysia has significant policy consequences and provides insightful information. The awareness of this association may help lawmakers create fiscal policies that encourage sustained economic growth, including the right tax rates, incentives, and structures. In addition, it can assist on the resource allocation, budget planning and forecasting of the future tax revenues.